Phase III randomised chemoprevention study with selenium on the recurrence of non-invasive urothelial carcinoma. The SELEnium and BLAdder cancer Trial. (December 2016) - Goossens, Maria E.; Zeegers, Maurice P.; van Poppel, Hendrik; Joniau, Steven; Ackaert, Koen; Ameye, Filip; Billiet, Ignace; Braeckman, Johan; Breugelmans, Alex; Darras, Jochen; Dilen, Kurt; Goeman, Lieven; et al.
Abstract: Background: In Belgium, bladder cancer (BC) is the fifth most common cancer in men. The per-patient lifetime cost is high. Previous epidemiological studies have consistently reported that selenium concentrations were inversely associated with the risk of BC. We therefore hypothesised that selenium may be suitable for chemoprevention of recurrence of BC. Method: The Selenium and Bladder Cancer Trial (SELEBLAT) was an academic phase III placebo-controlled, double-blind, randomised clinical trial designed to determine the effect of selenium on recurrence of non-invasive urothelial carcinoma conducted in 14 Belgian hospitals. Patients were randomly assigned by a computer program to oral selenium yeast 200 μg once a day or placebo for three years, in addition to standard care. All study personnel and participants were blinded to treatment assignment for the duration of the study. All randomised patients were included in the intention to treat (ITT) and safety analyses. Per protocol analyses (PPAs) included all patients in the study three months after start date. Results: Between September 18, 2009 and April 18, 2013, 151 and 141 patients were randomised in the selenium and placebo group. Patients were followed until December 31, 2015. The ITT analysis resulted in 43 (28%; 95% CI, 0.21–0.35) and 45 (32%; 95% CI, 0.24–0.40) recurrences in the selenium and placebo group. The hazard ratio (HR) was 0.85 (95% CI, 0.56–1.29; p = 0.44) while the HR for the PPA resulted in 42 and 39 (28%; 95% CI, 0.20–0.35) recurrences in the selenium and placebo group (HR = 0.96 [95% CI, 0.62–1.48]; p = 0.93). Conclusion: Selenium supplementation does not lower the probability of recurrence in BC patients. Highlights: The Selenium and Bladder Cancer Trial (SELEBLAT) study was a phase III placebo-controlled, double-blind, randomised clinical trial. SELEBLAT determined the effect of selenium on recurrence of non-invasive urothelial carcinoma. In total, 151 and 141 patients were randomised in the selenium and placebo group. The hazard ratio was 0.85 (95% CI; 0.56–1.29) (p = 0.44) for the intention to treat analysis. Selenium supplementation does not lower the probability of recurrence in bladder cancer.